2022
DOI: 10.3390/microorganisms10040702
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Hydrolates: Potential Tools for Defense against Bacterial Plant Pathogens

Abstract: The essential oils (EOs) of Origanum compactum and Satureja montana chemotyped (CT) at carvacrol, two Thymus vulgaris CT at thujanol and thymol, and Hydrolates (Hys) of S. montana and Citrus aurantium var. amara were chosen for studying their bactericidal efficacy against few phytobacterial pathogens. The Minimal Inhibitory Concentration (MIC) and Bactericidal Concentration (MBC) were found by microdilution assay. The essential oils of O. compactum (MBC 0.06% v/v), T. vulgaris CT thymol (MBC 0.06% v/v), and Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In this scenario, discovery and development of new drugs is urgently needed to combat the increase of fungal azole resistance. Nowadays, essential oils (EOs), alone or in combination with conventional drugs, are used to fight human pathogens, including multidrug-resistant ones ( 16 to 19 ). EOs are mixtures of natural substances obtained from the distillation or pressing of aromatic plants with a known antimicrobial activity ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, discovery and development of new drugs is urgently needed to combat the increase of fungal azole resistance. Nowadays, essential oils (EOs), alone or in combination with conventional drugs, are used to fight human pathogens, including multidrug-resistant ones ( 16 to 19 ). EOs are mixtures of natural substances obtained from the distillation or pressing of aromatic plants with a known antimicrobial activity ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they play a defensive role against predators and diseases. This role is related to their antifungal [20], antiviral [21] and antibacterial [22] activity thus ensuring plant protection [2].…”
Section: Mechanisms Of Essential Oils Actionmentioning
confidence: 99%
“…manihotis in vitro and in vivo conditions [44]. Proto et al [22] found that the essential oil of Origanum compactum (at 0.03% v/v) showed resistance induction in tomato plants against Xanthomonas vesicatoria infections. The same authors noted that the essential oils of Origanum compactum and Thymus vulgaris resulted in being the most effective against Erwinia amylovora under in laboratory conditions.…”
Section: Anti-bacterial Activitymentioning
confidence: 99%
“…Hydrosols have recently started to receive a lot of credit in a variety of areas, such as food (e.g., flavouring, preservatives, and sanitisers) [ 18 , 19 ], cosmetic and perfumery [ 20 ], aromatherapy [ 21 ], agriculture (e.g., biopesticides and repellents) [ 22 ], pharmaceutical (e.g., natural antibiotics, antioxidants and anti-inflammatory agents) [ 17 , 23 ], and medical (e.g., antimicrobial and antitumor agents) [ 24 ]. According to circular economy principles, using industrial by-products can be a sustainable way to address the environmental problems caused by waste discharging.…”
Section: Introductionmentioning
confidence: 99%